Foreign exchange interventions and monetary policy: evidence from emerging economies - Bui Trung Thanh (Review of Economic Perspectives, 2024)
The role of foreign exchange interventions in monetary policy conduct is an ongoing debatable issue, especially in inflation-targeting emerging economies, where monetary authority can follow other targets rather than price stability. This paper examines whether interventions in foreign exchange markets affect the setting of interest rates in countries where price stability is the main target of monetary policy. We used the ARDL model to investigate the matter of the intervention policy as well as its asymmetric impacts on monetary policy. The results provide evidence of the significant effect of foreign exchange interventions on monetary policy in inflation-targeting emerging economies, implying the existence of fear of floating. Particularly, interest rate changes can mitigate or accommodate the intervention policy, depending on countries. Furthermore, the interventions have asymmetric effects on monetary policy, showing the bias toward sales interventions. While sales interventions play a more pronounced effect in most emerging economies, excepting for Mexico where purchase intervention effect is of more importance.